Pengaruh Tata Ruang dan Atmosfer Website Toko Online Terhadap Emosional Konsumen Toko Online Blibli.com Pada Mahasiswa Universitas Negeri Padang - Irfan Maulana; Susi Evanita (Universitas Negeri Padang, 2019)
The purposes of this research are to analyze (1) the influence of Design Layout on Emotional Consumer (2) Influence atmosphere of Online Store on emotional Consumer. The population in this research is the students of Padang State University. The samples were selected using Non Probability Purposive Sampling where the total of the samples are 100 employees. The data were collected by using a survey with a questionnaire. The data were analyzed by using multiple regression analysis. The result of this research show (1) Design Layout has a negative and significant relationship on Emotional Consumer (2) Atmosphere of Online Store has a positive and significant relationship on Emotional Consumer. Keywords: Design Layout , Atmosphere of Online Store, Emotional Consument.